Luminescent and scintillating properties of lanthanum fluoride nanocrystals in response to gamma/neutron irradiation: Codoping with Ce activator, Yb wavelength shifter, and Gd neutron captor - Vargas, Jose Marcelo (2016)
A novel concept for gamma radiation detection and spectroscopy, and detection of thermal neutrons based on co-doped lanthanum fluoride nanocrystals containing gadolinium is presented. The trends of colloidal synthesis of the mentioned material, LaF3 co-doped with Ce3+ as the activator, Yb3+ as the wavelength-shifter and Gd3+ as the neutron captor, is reported. Nanocrystals of the mentioned material were characterized by transmission electron microscopy, X ray diffraction, energy dispersive X ray spectroscopy, optical absorption, and photoluminescence spectroscopy. Gamma detection and its potential spectroscopy feature have been confirmed. The neutron detection capability has been confirmed by experiments performed using a 252Cf neutron source.